Estimation of total phenolic, total flavonoid content and evaluation of anti-inflammatory and antioxidant activity of Ixora coccinea Linn. stems - R, Surana A; D, Wagh R (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
Ixora coccinea Linn. (Rubiaceae) has mentioned in Ayurveda as Paranti and traditionally stems used in inflammatory diseases like sprains, eczema, contusions and boils.Â Present study deals with evaluation of anti-inflammatory and antioxidant activity of extracts of I.coccinea stem. Anti-inflammatory activity was studied in vivo by carrageenan-induced paw edema in rat and in vitro by human red blood cell membrane stabilization method. Total tannin and flavonoid content of extracts was determined by using the Folin- Ciocalteu method and aluminum chloride method, respectively. Antioxidant activity was evaluated by in vitro assay involving nitric oxide scavenging, hydrogen peroxide scavenging, 2,2-Â diphenylpicrylhydrazyl (DPPH) radical scavenging, and ion chelating activity. Chloroform extract showed significant reduction in carrageenan induced rat paw edema (p<0.05) and protection of HRBC in hypotonic solution. Methanol extract contain more total tannin and flavonoid content as compared with petroleum ether and chloroform extract. All extracts showed concentration dependant free radical scavenging activity. Methanol extract and chloroform extract have shown better antioxidant activity and due to this antioxidant nature might be responsible for its anti-inflammatory activity. These activity supports to use of I.coccinea extract in traditional used in treatment of various inflammatory disaeses.